2017
DOI: 10.1097/scs.0000000000003627
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors Involved in Mandibular Prognathism

Abstract: Mandibular prognathism is defined as an abnormal forward projection of the mandible beyond the standard relation to the cranial base and it is usually categorized as both a skeletal Class III pattern and Angle Class III malocclusion. The etiology of mandibular prognathism is still uncertain, with various genetic, epigenetic, and environmental factors possibly involved. However, many reports on its coexistence in both twins and segregation in families suggest the importance of genetic influences. A multifactori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 59 publications
1
60
0
4
Order By: Relevance
“…It has also been reported that there is a left-right difference in the phenotype of muscle, such as contraction characteristics 16) . It is thought that genetic factors are involved in the onset of jaw deformities 2,3,17) ; however, it is difficult to explain left-right morphological differences, and it is assumed that some acquired, habitual, or local factors are also involved. Since hyperplasia of the mandibular head may be involved in neoplasia, hyper-/hypoplasia of the mandibular head was excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that there is a left-right difference in the phenotype of muscle, such as contraction characteristics 16) . It is thought that genetic factors are involved in the onset of jaw deformities 2,3,17) ; however, it is difficult to explain left-right morphological differences, and it is assumed that some acquired, habitual, or local factors are also involved. Since hyperplasia of the mandibular head may be involved in neoplasia, hyper-/hypoplasia of the mandibular head was excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
“…S obzirom na to da je naš pacijent progeničar i prošao je pubertetski vrhunac rasta, on je kandidat za ortognatsku kirurgiju 6 . Progenija ili mandibularni prognatizam je nasljedna skeletna malokluzija [6][7][8] . U našoj populaciji je zastupljena oko 5 % u trajnoj denticiji 9 .…”
Section: Raspravaunclassified
“…caries, injuries, oral parafunctions (such as bruxism) [5,6,7]. The aetiology of malocclusion is primarily genetic [8,9,10]. Possible etiologies include genetic and environmental factors or a combination of both [11].…”
Section: Introductionmentioning
confidence: 99%